La evasión de impuestos en la actividad financiera y tributaria, causas y consecuencias - JIMENEZ JAYA, CARMITA LORENA (2017)
This study is one of the goals, determine how dependent individuals evade taxes, and is through a descriptive and explanatory research, it seeks to establish the cause of a behavior evasion tax, which is called tax evasion. For this reason it is important the analysis of tax fraud, the effects caused to the economy and declining revenues as necessary to the General State Budget, whereas the part of tax revenues is the one to cause greater impact redistributive tax revenues; this tax fraud is a phenomenon that besides eroding government revenues and cause a harmful effect on tax revenues, deteriorating economic and social structure of the country in breach of the legitimacy of governments, overriding priorities of the economy, causing an assignment inefficient use of resources. The most common tax evasion in our country is on the income tax, and is one of the main phenomena affecting the Tax Systems and tax revenue as state revenues decline, resulting in insufficient resources required to meet the collective needs, weakening the economy, so it is important to study. Another goal we set ourselves is to analyze the causes and incidences of tax evasion in Ecuador, seeking to establish mechanisms to control and reduce it. For that, we will start the study of the tax system and taxation of Ecuador, then the causes of tax evasion will be established, the tools used by taxpayers to evade, and ultimately presents alternatives to control and reduce it. For a more extensive knowledge in tax matters, is defined to taxes, their nature and characteristics are determined, the types of taxes that are identified: taxes, fees and special assessments or improvement, as a basis for this research; likewise a detailed analysis concerning taxpayers and their classification, administrative procedures for sanctions for tax violations, whether violations, missing or regulatory offenses under the case is made. The expedition and the amendments to the various legal norms in Ecuador, have given to the tax authorities and other entities control a tool to combat tax evasion and tax avoidance, but unfortunately in practice has not created a culture tax conscious, and as understood in legal matter, it is our obligation to put more emphasis on dissemination, about the harm this tax evasion. According to the Tax Code, is defined as fraud, any intentional act of simulation, concealment, omission, misrepresentation or deception to mislead in determining the tax liability, or which fails to pay all or part of the taxes actually due, in himself or herself or a third party; as well as any intentional conduct that contravene or impede the control work, determination and punishment exercised by the tax administration. Tax avoidance is the non-payment of contributions lawfully, ie, takes advantage spaces or gaps in the law and thus is not located in the standard hypothesis. Fiscal or tax evasion, however, is any elimination or reduction of tax amount produced within the scope of a country, who are legally bound to pay it and they achieve this result through fraudulent conduct or omissions by violating laws. In the second part, based on the results of the surveys, we find the main methods that possibly would be used by taxpayers to consummate fiscal fraud such as failure to issue bills of sale, fraudulent issuing of credit notes, make sales below the market and increase costs and expenses fictitious invoices and undue costs and expenses increased prices.